Addressing Global Challenges: Indonesia’s Pursuit of Tuberculosis Eradication - Denny Yarmawati; Apriwan (Journal of Governance and Global Studies, 2026)
This paper explores how shifting dynamics in international politics impact tuberculosis (TB) control efforts in Indonesia—currently the world’s second-highest TB burden country. With a national target to eliminate TB by 2030, Indonesia’s success hinges on sustained global health cooperation, stable funding, and resilience in its pharmaceutical supply chain. However, geopolitical changes—particularly the reorientation of U.S. foreign policy and the potential dismantling of USAID—pose significant threats to global health governance. The weakening of major institutions such as the WHO and the Global Fund, both heavily reliant on U.S. support, risks undermining Indonesia’s progress. These organizations provide crucial normative guidance, technical expertise, and financial resources to Indonesia’s TB programs. Their diminished capacity would have both direct and cascading effects on national efforts. The paper argues that Indonesia’s reliance on multilateral mechanisms renders it vulnerable to disruptions in global health leadership, raising critical questions about the sustainability and sovereignty of its TB response.